Cerai Gugat Dengan Alasan Yang Dibuat-Buat Perspektif Qowaid Al-Fiqhiyah - M Mohsi (ASASI: Journal of Islamic Family Law, 2021)
Marriage is a sacred bond that every couple wants to last forever. No one in a marriage wants a divorce, but in the course of marriage it is possible that there will be problems that will befall a family which can lead to quarrels, even to the point of divorce. This study elaborates on divorce with fictitious reasons. This study uses a qualitative paradigm, with a conceptual approach that focuses on the study of qaidah fiqh. This study tries to conduct a study on divorce from the perspective of qaidah fiqh, from the perspective of qaidah fiqh to lawsuits for divorce using artificial reasons. Divorce in the perspective of Qawaid al-Fiqhiyah is permissible, of course, by using reasons permitted by sharia. While suing for divorce with trumped-up reasons, the law is not allowed.